The Icon of the Holy Trinity with Acts from the Dormition Cathedral of the Tikhvin Monastery. Problems of Dating and Interpretation - Shalina, Irina A. (Actual Problems of Theory and History of Art, 2019)
The origins of the illustrated cycles of the “wanderings” of the Holy Trinity are usually connected with the mid-16th century, a time when after the Moscow Kremlin Fire (1547) new icons for the royal Annunciation Church were commissioned from the Pskov and Novgorod masters. The border scenes of the new icon of the Old Testament Trinity became one of the central themes of the Case of Diak Viskovaty and the conciliar sessions which followed (1553–1554). The “Doubts and Outrage” of I. Viskovaty were causedby the newly-painted image of Christ, depicted as an Angel, with the octagonal halo of Saint Sophia, the Wisdom of God (seen by some theologians as the ultimate depiction of the Second Hypostasis of the Trinity before the Incarnation). Viskovaty saw a fundamental flaw and temptation in such depictions, since they might have presumed that the Lord took up not only the human nature, but also the angelic. The original icon from Kremlin did not survive, but it is widely believed that its iconographic composition was replicated in all depictions of the Holy Trinity with Acts, painted in the middle and second half of the 16th century. One of these (as traditionally upheld in the academic world) was the icon from Tikhvin, now in collection of theState Tretiakov Gallery, which is surrounded by 24 border scenes that illustrate not only the Book of Genesis and the “wanderings” of the Angels, but also the Life of the Theotokos, Gospel scenes and the Akathistos.Yet it is worth noting that the unique iconographic composition of the given piece, the striking traits of itsstyle and artistry give us every reason not only to attribute the icon to Pskov masters, but also to consider it the oldest among such images. The iconographer clearly retains the volume and proportional balance of thefigures, the softness of the facial depictions, the color work, the generous use of the gold hatching. All of these elements allow us to consider this icon a work of art from the dawn or first quarter of the 16th century. The icon in question follows the same tradition in Pskov art that brought us the Fiery Ascension of the Prophet Elijah (State Museum of History) and the Old Testament Trinity (State Tretiakov Gallery), but stands apart in its subtle color pallet and lack of ornamentation.The centerpiece of the icon, as well as the border scene of “Acts” follow the unique iconographic variations, known only in Pskov. The original interpretation of these themes can easily be justified, since the dedication of the Cathedral to the Holy Trinity is clearly linked with the prolonged evolution of the Trinitarian iconography. All of the border scenes can be split into two thematic categories. The major part (border scenes 1–14) is dedicated to the Book of Genesis. The lesser — to the Gospel narrative and Akathistos hymns. There is reason to believe that this unusual combination of border scene themes, surrounding the Holy Trinity, originated exclusively in Pskov in the late 15th century. The outermost border scenes in the lower tier — depicting Saint Sophia (the Wisdom of God) and the Dormition — coincide directly with the dedication of the Dormition Cathedral in the Tikhvin Monastery, which was part of the Diocese of Novgorod. Since the icon originates from that exact monastery, one should believe that it was painted for the consecration of the Cathedral in 1515.
Keywords: Old Russian art; Russian painting of the late 15th — early 16th century; Russian icon painting; Pskov; style; iconography; Tikhvin; monasteries; the icon of the Holy Trinity; iconostasis; border scenes with Acts; Book of Genesis